BATAS PERSINGGUNGAN KEWENANGAN MENGADILI SENGKETA HAK MILIK ANTARA PENGADILAN AGAMA DENGAN PENGADILAN NEGERI - Mustating Daeng Maroa; Arianti A Ogotan (Jurnal Yustisiabel, 2020)
This research aims to examine the scope of the authority of the Religious Court in prosecuting a case and to review the limits of the tangent of authority in adjudicating property disputes between the Religious Court and the District Court. This research is normative juridical with primary, secondary and tertiary legal sources. The results showed that the scope of the authority of the Religious Court in prosecuting certain cases is to examine, break, and resolve cases in the first level between people who are Muslims in the field of marriage, heirs, wills, grants, endowfafs, zakat, infaq shadaqah and sharia economics. While the limit of the tangent of authority in adjudicating a property dispute between the Religious Court and the District Court is determined by the filing of a dispute to the Religious Court then must meet three conditions that the subject of the dispute law must be muslim, the object of the dispute raised is the same as the object of the dispute which becomes the absolute authority of the Religious Judiciary as well as the dispute of property rights with the dispute that becomes the absolute competence of the Religious Judiciary has interconnected legal consequences